Exploring Effects of Creativity Training on Default Mode Network and Attention - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2019)
The growing consensus is that creativity is associated with connectivity across multiple neural networks including, but not restricted to, networks involved in executive and cognitive control along with regions closely linked to the Default Mode Network (DMN) of the brain. In this study, the effects of a nine-week creativity training given to managers with a minimum of five years of experience in their field was explored. Power Spectral Density computed from scalp electrical signals and P300 waves derived from ERP techniques paired with Kaufman Domains of Creativity Scale (K-DOCS) were used. After the training, an increase in "Everyday" creativity was observed, implying that this aspect of creativity is possibly more dependent on the processing of the DMN than on attention and executive function. © 2019 Chamber of Turkish Electrical Engineers.